Manajemen Pembelajaran Pendidikan Agama Islam pada Perceraian Orang Tua Terhadap Perilaku Anak di Desa Tumbang Runen Kecamatan Kamipang Kabupaten Katingan - Muhammad Tri Ramdhani (Jurnal Hadratul Madaniyah, 2017)
The opening of the divorce door in Islam is not as easy as we think because there are ties or boundaries and norms that must be fulfilled. Allah Almighty never justifies something he hates the most but divorce and Shari'a solely as a way out of eternal bickering. Separation is a very big influence on the continuity of religious education of children, because if there is divorce many parents release responsibility for their children . Problem formulation in this research is: a) How does the child's behavior impact after her parents divorce ? b ) How is the government's efforts to deal with parental divorce? The research approach using qualitative descriptions, with the subject 5 people KK. The techniques used are observation, interview, and documentation, which are validated through triangulation and analysis in 3 stages: data collection , data reduction , and conclusions. The results of the research are The impact of children's behavior after their parents divorced including children joining in smoking and drinking and worship children began to rarely pray, especially praying in congregation in the mosque, Government efforts in overcoming the occurrence of divorce among parents prevent early marriage, advice in recitals, and providing guidance when there is a dispute between husband and wife before the divorce decision.